Buying and Selling Domestic Animals in the Folk Polish Culture - Kielak, Olga (Literatura Ludowa. Journal of Folklore and Popular Culture, 2020)
In the traditional Polish culture, animals from the closest human environment (cattle, horses and pigs) were the most frequently bought and sold goods. The echoes of old commercial transactions can still be heard in the dialect (“tail”, “horn”, and “hoof” animals). However, it would not be possible to reconstruct the purchase and sale of domestic animals in the Polish language without using the co-linguistic data (beliefs and practices) which coincide with and complement the perfunctory information on transactions recorded in language. The sale and purchase of animals was connected with a number of procedures performed before and after the transaction, aimed at facilitating the sale and ensuring the seller’s and buyer's success in breeding. Using the methodology developed for Lublin Dictionary of Stereotypes and Folk Symbols, I look at the cultural mechanisms of selling and purchasing animals. This analysis enables me to show the place occupied by domestic animals in the world of folk values.